Effects of age and gender on the serum levels of clozapine, olanzapine, risperidone, and quetiapine. (2nd September 2017) - Castberg, I.; Westin, A. A.; Skogvoll, E.; Spigset, O.
Abstract : Objective: To investigate serum concentrations of second‐generation antipsychotics in relation to age and gender in a population ranging from 18 to 100 years. Method: Results from a routine therapeutic drug monitoring database were retrieved, and 43 079 samples from 11 968 patients were included (17 249 samples for clozapine, 16 171 samples for olanzapine, 5343 samples for risperidone, and 4316 samples for quetiapine). The dose‐adjusted concentration was used as the primary target variable. A linear mixed model was used to allow the inclusion of multiple samples from each patient. Results: Age had a significant impact on the concentrations of all four drugs. At the age of 80, the dose‐adjusted concentrations were up to twice those of the age of 40. At the age of 90, dose‐adjusted concentrations were two‐ to three‐fold higher. Age‐related increases were largest for clozapine (+108% at 80 years; +197% at 90 years) and smallest for olanzapine (+28% at 80 years; +106% at 90 years). Females generally had dose‐adjusted concentrations 20–30% higher than males. Conclusion: The effect of age on the serum concentrations of the antipsychotics studied becomes pronounced with advanced age. The patient population aged above 70 should be subdivided according to exact age, and considerable dose reductions are recommended.